The Role of Literature in the Processes of Destereotyping (Through Examples from Macedonian Literature) - Marija Gjorgjieva Dimova (Slavia Meridionalis, Institute of Slavic Studies, Polish Academy of Sciences, 2022)
The Role of Literature in the Processes of Destereotyping (Through Examples from Macedonian Literature) Considering the imagological conceptions of the Other by Daniel-Henri Pageau and Gordana Đerić, this text analyses the role of literature in the deconstruction of stereotypes that circulate in communication between Balkan neighbours. In the focus of our interpretation are three novels of contemporary Macedonian literature (Luan Starova’s Balkanvavilonci, Dragi Mihajlovski’s Mojot Skenderbej and Blazhe Minevski’s Nishan), which are paradigmatic in two ways: 1. they refer to historical events and figures, thus confirming that history is the basic mechanism for the argumentation of stereotypical images; 2. they depict processes of destereotyping both thematically and structurally, but also by their appearance in a particular sociohistorical context, with the aim of promoting supranational, universal, human, civilizational, and cultural values such as love, empathy, forgiveness, dialogue, tolerance, education, love of books, optimism, humaneness, all of which are usually treated as originally European values. Literature, by articulating the processes of destereotyping through the narrative strategies in the works, confirms that it holds the potential to act correctively on systems where different forms of power are based on discrimination and submission
Keywords: stereotype, destereotypization, depiction of the other/neighbour, Macedonian literature, contemporary novel